Paradoks Integritas Pemimpin Kristen dalam Menghadapi Polarisasi Politik dan Identitas Kelompok di Toraja - Raden Palipungan; Dia Bato Salle; Irma Yanti Markus; Tamar Tangke; Agustina Pare; Angelin Risty Daud Samara (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
This research examines the paradox of Christian leader integrity in facing political polarization and group identity in Toraja society. The background of the problem is a contradictive phenomenon where Christian communities strongly emphasize ethical character of leaders, yet strong group identification can blind them to ethical inconsistencies of supported leaders, especially in the dynamics of regional and presidential elections that divide churches. This research aims to analyze the paradox of Christian leader integrity, identify psychological, theological, and sociological factors causing ethical blindness, and formulate leadership principles that can maintain integrity amid political pressure. Using qualitative descriptive methods based on literature study, this research collects data from leadership theology literature, group identity psychology, and empirical studies on political practices in Toraja Christian communities. Research findings show that the integrity paradox manifests in local political dynamics where ethical standards become loose when leaders come from the same identity group. Factors causing ethical blindness include in-group bias and cognitive dissonance (psychological), sacred-secular dualism and permissive interpretation (theological), as well as clan structure and conformity pressure (sociological). The formulated leadership principles include commitment to biblical standards, theology-based political education, transformative prophetic role, accountability systems, contextual leadership, and building mature faith communities. The implication is that this research provides theoretical contributions to the development of contextual leadership theology and practical recommendations for church leaders in navigating the complexity of identity politics. Research recommendations include developing theology-based political education programs in churches, building leadership accountability systems, and further empirical research to validate the conceptual framework that has been built.